Reconstructing Ijtih?d in Unifications the Islamic Calendar: Jasser Auda's Maq?shid al-Shar?`ah Approach - Muh Rasywan Syarif; Sakirman (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2025)
The determination of the beginning of the Hijri month often triggers differences among Muslims due to differences in methods between rukyat (hilal observation) and hisab (astronomical calculation), which have an impact on social fragmentation and uncertainty in the implementation of worship. This study offers a reconstruction of ijtih?d in determining the beginning of the Hijri month through Jasser Auda's maq?shid al-shar?'ah approach, which emphasizes holistic thinking, openness to change, and orientation to the benefit of the people. This research responds to two questions: (1) How can the maq?shid al-shar?'ah approach reconstruct ijtih?d in determining the beginning of the Hijri month? and (2) To what extent can unification of the Islamic calendar be achieved through the integration of rukyat and hisab methods based on maq?shid principles? The research method is qualitative with literature analysis and comparative study of classical fiqh books, contemporary fatwas, and astronomical documents related to the Neo-MABIMS criteria. The results show that this approach allows synergistic rukyat-hisab integration, strengthens legal certainty, accommodates the development of hilal observation technology, and makes the benefit and unity of the ummah as the top priority, in line with the principles of ?if? al-d?n, ?if? al-'aql, and ?if? al-ummah. This reconstruction of ijtih?d offers a new paradigm that is strategic, contextual, and inclusive, as a solution to reduce socio-theological differences and build a uniform and sustainable Islamic calendar